Post-Divorce Mut’ah: The Reinforcement of Gender Hierarchies in the Practice of Religious Courts - Rafiqa Izzati, Nida (USRATY : Journal of Islamic Family Law, 2025)
This study investigates the role of post-divorce mut’ah (a form of consolatory gift from husband to wife) in reinforcing gender hierarchies within the religious court system in Indonesia. The primary aim is to explore how mut’ah is conceptualized, negotiated, and decided upon in courtrooms, and how this process reflects broader socio-religious power relations between men and women in post-divorce contexts. Employing a qualitative research method, this study is based on in-depth interviews with judges, divorced women, and legal advocates in three religious courts across Java and Sumatra. In addition, courtroom observations and analysis of case documents were conducted to understand how mut’ah claims are framed and adjudicated. The findings indicate that although mut’ah is formally recognized under Islamic legal doctrine and Indonesian religious court jurisprudence, its implementation remains inconsistent and highly gendered. Judges often interpret mut’ah as non-obligatory and discretionary, resulting in many divorced women being denied this right, especially in cases where the woman is perceived as “at fault.” The courtroom discourse often reaffirms patriarchal norms, positioning women as dependent and less entitled to post-divorce economic justice. The study concludes that rather than serving as a mechanism of gender equity or compensation, mut’ah in practice tends to reproduce gendered power imbalances. Academically, this research contributes to the fields of Islamic legal studies, gender and law, and socio-legal anthropology by highlighting how legal institutions mediate religious interpretations in ways that reinforce structural inequalities, particularly in the realm of family and marital dissolution in contemporary Muslim societies.